Reduction of water and energy consumption in the sanitary ware industry by an absorption machine operated with recovered heat. (10th April 2021) - Cuviella-Suárez, Carlos; Colmenar-Santos, Antonio; Borge-Diez, David; López-Rey, África
Abstract: Water scarcity is a real problem that affects directly over one third of the world population, and greenhouse gases only worsen the situation. Due to this, action must be taken against the overexploitation of resources. Water accounting and saving should be mandatory for a proper sustainable industry. In this regard, the sanitary ware industrial sector, as an intensive consumer of water, should make a social commitment to contribute to stopping water overuse. Sanitary ware manufacturing delivers an amount of water equivalent to the half of the total production weight via evaporation. The aim of this research was to find a green process to reuse the evaporated water and thereby reduce the overall water consumption level as well as promote a cleaner technology with low environmental impact. The key point in supporting sustainability restriction is to match water condensation with heat recovery to avoid any energy surplus. The thermal energy recovered from kiln exhaust gets transferred into a cold flow, which condenses the evaporated water by an absorption cycle. Computational modeling was used to thermodynamically analyze and optimize the performance of this novel technology. The proposed model was applied to the most extended technologies to reduce natural gas usage by 25% and total water usage by 16%. Besides, the surplus of condensed water from combustion and from air moisture has been quantified to be added to savings. The present research provides a practical tool for the sector to use in designing more efficient, green manufacturing plants while supporting a more sustainable business model. It demonstrates and quantifies the potential of water saving in the sanitary ware industry, which had never before been tackled. Graphical abstract: Image 1 Highlights: Water consumption reduction in a sanitary-ware factory is presented and validated. Heat recovery from kiln provides energy for the water treatment by absorption. Water management accounting has to be included in any environmental management accounting. Proposed method produces reductions of resources and economic improvements.